2017
DOI: 10.1007/s00535-017-1404-4
|View full text |Cite
|
Sign up to set email alerts
|

Human hepatic stellate cell isolation and characterization

Abstract: The hepatic stellate cells (HSCs) localize at the space of Disse in the liver and have multiple functions. They are identified as the major contributor to hepatic fibrosis. Significant understanding of HSCs has been achieved using rodent models and isolated murine HSCs; as well as investigating human liver tissues and human HSCs. There is growing interest and need of translating rodent study findings to human HSCs and human liver diseases. However, species-related differences impose challenges on the translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
168
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(168 citation statements)
references
References 117 publications
(183 reference statements)
0
168
0
Order By: Relevance
“…The discovery of compounds capable of preventing HSC activation might therefore lead to effective therapies for liver cirrhosis . Hepatic stellate cells express at least two type III intermediate filaments, desmin and GFAP; desmin is utilized as a marker for both quiescent and activated HSCs in vivo , and GFAP is a marker for quiescent HSCs . In this study, we found that chronic CCl 4 ‐treated rats showed an increase in total HSCs, as shown by increments in desmin and GFAP proteins.…”
Section: Discussionmentioning
confidence: 56%
“…The discovery of compounds capable of preventing HSC activation might therefore lead to effective therapies for liver cirrhosis . Hepatic stellate cells express at least two type III intermediate filaments, desmin and GFAP; desmin is utilized as a marker for both quiescent and activated HSCs in vivo , and GFAP is a marker for quiescent HSCs . In this study, we found that chronic CCl 4 ‐treated rats showed an increase in total HSCs, as shown by increments in desmin and GFAP proteins.…”
Section: Discussionmentioning
confidence: 56%
“…Blood samples were collected for the analyses of liver functions including GPT/ALT (alanine aminotransferase), GOT1/AST (aspartate aminotransferase), and TBIL (total bilirubin). Moreover, primary human HSCs were isolated from the collected liver tissue by laser capture microdissection (LCM) as described previously [39][40][41], and total RNAs were extracted for RNA-Seq. The data revealed that 1024 mRNAs were upregulated and 831 mRNAs were downregulated in sorafenib-treated human HSCs as shown in the heat map (Figure 8(a)) and volcano plot (Figure 8(b)).…”
Section: Elavl1 Upregulation Ferritinophagy Activation and Ferroptomentioning
confidence: 99%
“…Blood samples were collected for the analyses of liver functions including GPT/ALT, GOT1/AST, and TBIL. Moreover, primary human HSCs were also isolated from the collected liver tissue by laser capture microdissection (LCM) as described previously [39][40][41], and total RNAs were extracted for RNA-Seq and real-time PCR.…”
Section: Human Liver Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Hepatic stellate cells are activated by chronic liver injury and undergo a morphological transition to fibroblast-like cells. 7 Under these conditions, the contraction of activated HSCs narrows the sinusoidal lumen and reduces hepatic microcirculatory flow, resulting in portal hypertension. 8 Furthermore, activated HSCs express α-smooth muscle actin (α-SMA) and produce profibrotic cytokines, such as transforming growth factor (TGF) and platelet-derived growth factor, which alter the extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%